2016
DOI: 10.3390/s16111785
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Copper(II) Ions Using Glycine on Hydrazine-Adsorbed Gold Nanoparticles via Raman Spectroscopy

Abstract: A facile, selective, and sensitive detection method for the Cu2+ ions in environmental and biological solutions has been newly developed by observing the unique CN stretching peaks at ~2108 cm−1 upon the dissociative adsorption of glycine (GLY) in hydrazine buffer on gold nanoparticles (AuNPs). The relative abundance of Cu species on AuNPs was identified from X-ray photoelectron spectroscopy analysis. UV-Vis spectra also indicated that the Au particles aggregated to result in the color change owing to the dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…In Figure 4 b, the absorption band was weakened for the cyanide-containing wastewater samples. This interpretation could also be supported by the relatively weak CN intensity at ~2114 cm −1 [ 29 ] of the wastewater after the alkaline chlorination treatment of sample “S2”, as shown in Figure 4 c.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…In Figure 4 b, the absorption band was weakened for the cyanide-containing wastewater samples. This interpretation could also be supported by the relatively weak CN intensity at ~2114 cm −1 [ 29 ] of the wastewater after the alkaline chlorination treatment of sample “S2”, as shown in Figure 4 c.…”
Section: Resultsmentioning
confidence: 60%
“…The detection limit of the current SERS method was found to be around ten times lower than that of the colorimetric test under our experimental conditions. The lowest concentration of our SERS detection of Cu 2+ in wastewater samples was around 1 ppm, which is lower than the Environmental Protection Agency permission level (1.3 ppm = ~20 μM) for drinkable water [ 29 ]. Figure 6 illustrates the alkaline chlorination process of the influent sample “S1” to remove the cyanide species in electroplating the industrial wastewater to produce non-cyanide wastewater “S2”.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In the present work, the MESP was prepared by hydrothermal method and hence the other possibility is through the protein component route. Collagen protein in egg shell is composed of mainly three amino acids-Glycine, Proline and Hydroxy proline [23]. The hydroxyl proline can react with aqueous copper sulfate solution to undergo reduction of Cu +2 to Cu°to form proline.…”
Section: Mechanism Of In Situ Generated Cunps and Cu 2 Onps In Mespmentioning
confidence: 99%
“…In recent years, several studies have reported on the use of amino acids such as L-cysteine, the glycine-histidine complex for the determination of copper ions based on electrochemical detection [9,10]. Glycine (Gly) is one of the simplest amino acids that can bind copper in a dimeric form [11].…”
mentioning
confidence: 99%